Efektivitas Program Ketahanan Pangan dalam Menangani Kasus Stunting di Kabupaten Asahan Tahun 2024 - Frisnoiry, Suci; Enjelika, Tri Nova; Siahaan, Bertua Marisi Gabryella; Dupa, Lidya Priska (Ikatan Da'i Indonesia, 2024)
Food is one of the basic human needs. If these needs are not met, both in quantity and quality at the individual and household levels, it will interfere with the achievement of a healthy, active and sustainable quality of life and can lead to various health and nutrition problems. Stunting is one of the chronic nutritional problems caused by low access and affordability to food. The purpose of this study was to analyze the relationship between household food security and the incidence of stunting in toddlers aged 6-23 months in Asahan Regency in 2024. This type of research is observational with a case-control design. The research sample was under-fives aged 6-23 months, totaling 126 for each case and control group with a ratio of 1:1. The sampling technique used the total sampling method. Data were analyzed in stages, namely univariate, bivariate and multivariate analysis. Bivariate statistical test using chi-square and multivariate using logistic regression. The results of the bivariate analysis showed that household food security was associated with the incidence of stunting in children aged 6-23 months (p=0.04, OR=2.70, 95% CI: 0.94-8.77). External variables that were significantly associated with the incidence of stunting in children aged 6-23 months were maternal height (p=0.00, OR=2.03, 95% CI: 1.14-3.65) and history of LBW (p=0.03, OR=3.02, 95% CI: 0.98-11.04). Multivariate analysis results